2020
DOI: 10.1108/cms-05-2019-0191
|View full text |Cite
|
Sign up to set email alerts
|

Employee strengths use and innovative behavior: a moderated mediation model

Abstract: Purpose This study aims to investigate the mediating role of positive affect and the moderating role of deficit correction in the relationship between employee strengths use and innovative behavior. Design/methodology/approach This study adopted a three-wave research design to gather data. A convenience sample of 189 employees working in diverse organizations in China was applied to examine the hypotheses. Findings The results indicated that employee strengths use was positively related to innovative behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
1
19
0
1
Order By: Relevance
“…The contemporary stems of interdisciplinary management science research investigating the associations of employees psychological reactions such as commitment, emotion, pride, respect, honor, satisfaction, identity, engagement, attitude, and organizational and socially responsible behaviors such as value co-creation behavior (Hur et al, 2021 ), productive behavior (Jurek & Besta, 2021 ), pro-environmental behavior (Cheema et al, 2020 ), innovative behavior (Ding et al, 2021 ), work addiction behavior (Brieger et al, 2020 ), extra-role behavior (Chaudhary, 2020 ), pro-citizenship behavior (Rice et al, 2021 ), green behavior (Kim et al, 2019 ), societal happiness (Chia et al, 2020 ), and societal behavior (SB; De Roeck & Farooq, 2018 ) have been expanded in the micro-corporate social responsibility (CSR) studies (Barnett et al, 2020 ; Hill et al, 2021 ; Hur et al, 2021 ; Jurek & Besta, 2021 ; Mahmud et al, 2021a , b ; Maon et al, 2021 ; Moon et al, 2020 ). CSR as a broad area of study is popularly identified as “the commitment of business to contribute to sustainable economic development, working with employees, their families and the local communities” (World Business Council for Sustainable Development, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The contemporary stems of interdisciplinary management science research investigating the associations of employees psychological reactions such as commitment, emotion, pride, respect, honor, satisfaction, identity, engagement, attitude, and organizational and socially responsible behaviors such as value co-creation behavior (Hur et al, 2021 ), productive behavior (Jurek & Besta, 2021 ), pro-environmental behavior (Cheema et al, 2020 ), innovative behavior (Ding et al, 2021 ), work addiction behavior (Brieger et al, 2020 ), extra-role behavior (Chaudhary, 2020 ), pro-citizenship behavior (Rice et al, 2021 ), green behavior (Kim et al, 2019 ), societal happiness (Chia et al, 2020 ), and societal behavior (SB; De Roeck & Farooq, 2018 ) have been expanded in the micro-corporate social responsibility (CSR) studies (Barnett et al, 2020 ; Hill et al, 2021 ; Hur et al, 2021 ; Jurek & Besta, 2021 ; Mahmud et al, 2021a , b ; Maon et al, 2021 ; Moon et al, 2020 ). CSR as a broad area of study is popularly identified as “the commitment of business to contribute to sustainable economic development, working with employees, their families and the local communities” (World Business Council for Sustainable Development, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…Organisations applying strengths use interventions to convey information and messages that making good use of strengths at work is encouraged and appreciated, which, in turn, leads to giving more back to the organisation in the form of positive workplace outcomes, innovation performance in this study . By implementing strengths-based interventions, organisations may create a supportive and open working environment, recognising and appreciating employee talents and strengths for further growth that may lead to more innovation performance (Ding et al, 2020). Therefore, this research suggests that a strengths-based psychological climate, where individuals feel appreciated and recognised due to exerting their strengths at work, may facilitate their feelings of self-worth, respect and competence, which, in turn, will result in better innovation performance.…”
Section: Strengths-based Psychological Climate and Employee Innovatio...mentioning
confidence: 86%
“…According to the JD-R model, job resources characterised by gain spirals, generate additional resources that are beneficial to improve employee positive outcomes at work through psychological motivation process (Bakker and Demerouti, 2017;Ding et al, 2018Ding et al, , 2020. Strengths-based psychological climate as one job resource represents individual perceptions towards organisational strengths-based interventions to develop their strengths may further influence individual attitudes and behaviour (Bakker and Demerouti, 2017;Ding et al, 2018).…”
Section: Strengths-based Psychological Climate and Employee Innovatio...mentioning
confidence: 99%
See 2 more Smart Citations